Christmas Eve on Sesame Street [videorecording (DVD)] - Oz, Frank; Nelson, Jerry, 1934-2012; Hunt, Richard, 1951-1992; Manzano, Sonia; McGrath, Bob; Spinney, Caroll; Singer, Dulcy; Stone, Jon; Bailey, Joseph A. (Sesame Street., 2001)
How does Santa get down all those skinny little chimneys? While trying to solve this riddle, Big Bird discovers that the true miracle of Christmas is the spirit of loving and sharing.